O IMPACTO DA AGRICULTURA SOBRE O MEIO AMBIENTE - Deus, Rafael Mattos de; Bakonyi, Sonia Maria Cipriano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705625 The development of humanity in recent times has changed the natural environment. Thesechanges, for the most part, are impacts on fauna and flora. In addition to the industries and thecity, these changes also have been affected by agriculture, there are the intensive growth andindiscriminate use of pesticides, of soil, of water, and of deforestation and intensive andprolonged monoculture - all these factors affect the environment, including man himself. Howeverthere are researches about alternative technology and ways to assist agricultural developmentwithout harming the environment, this is what the laws and conferences propose for sustainabledevelopment. An example is the use of natural substances to prevent pests, rather thanagricultural chemicals. Water, for example, can be used with more rational or by drip irrigation,that shows a great saving of water and better development of the plants. Therefore this studyaimed to show the role of agriculture in the decadence of sustainability, but also reviews the existing technologies and alternatives to allow the development of both environment andagriculture.